Methods of drying and maintaining the quality of agricultural products - Samadov Muhiddin Akhadovich (Periodica Journal, 2024)
This scientific article provides an overview of various methods of drying agricultural products and examines their effectiveness in maintaining product quality. Drying is an important process in agriculture, helping to reduce moisture, extend shelf life, and prevent spoilage of harvested crops. The article discusses traditional drying methods such as sun drying and air drying as well as advanced methods such as hot air drying, freeze drying and vacuum drying. It also examines the effects of drying methods on product quality attributes, including nutritional value, color, flavor, and texture, and highlights strategies for maintaining quality during drying
Keywords: methods; agricultural products; quality control; traditional drying